Co-Design of a 3D Virtual Campus for Synchronous Distance Teaching Based on Student Satisfaction: Experience at the University of Almería (Spain) - Óscar González-Yebra; Manuel A. Aguilar; Fernando J. Aguilar; Manuel Lucas (MDPI AG, 2019)
This study presents the main advances made in recent years by an innovative teaching group at the University of Almeria, who are attempting to incorporate alternative spaces for teaching-learning interaction. This group is developing a new line of study to obtain the main vectors for creating an accessible 3D virtual campus on the Second Life platform, recognized as a multi-user virtual environment (MUVE). The goal of this work was to measure the satisfaction and perception of a group of university students. To do this, a co-design approach based on student opinions by relating methodological procedures with an adaptation of the Kano model usually used for product design has been followed. The results found by a panel of postgraduate students in the second stage of the educational project, suggest that the synchronous distance teaching proposal developed can effectively facilitate conciliation of family, work and personal life with online teaching-learning. In the case of undergraduate students with class attendance, the use of the 3D virtual campus is perceived as something more complementary.